Coherent ψ(2S) photo-production in ultra-peripheral Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Busch, Oliver; Fleck, Martin; Glässel, Peter; Klein, Jochen; Knichel, Michael Linus; Leardini, Lucia; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; et al. (Physics letters, 2015)
We have performed the first measurement of the coherent ψ(2S) photo-production cross section in ultra-peripheral PbPb collisions at the LHC. This charmonium excited state is reconstructed via the ψ(2S)→l+l− and ψ(2S)→J/ψπ+π− decays, where the J/ψ decays into two leptons. The analysis is based on an event sample corresponding to an integrated luminosity of about 22 μb−1. The cross section for coherent ψ(2S) production in the rapidity interval −0.9<y<0.9 is dσψ(2S)coh/dy=0.83±0.19(stat+syst) mb. The ψ(2S) to J/ψ coherent cross section ratio is 0.34−0.07+0.08(stat+syst). The obtained results are compared to predictions from theoretical models.
*ALICE Collaboration: J. Adam, V. Anguelov, O. Busch, M. Fleck, P. Glaessel, J. Klein, M.L. Knichel, L. Leardini, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, M.A. Voelkl, B. Windelband, M. Winn, A. Zimmermann [und 954 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 19.07.2021